Toxicity of titanium dioxide nanoparticles on Pseudomonas putida. (1st March 2016) - Combarros, R.G.; Collado, S.; Díaz, M.
Abstract: The increasing use of engineered nanoparticles (NPs) in industrial and household applications will very likely lead to the release of such materials into the environment. As wastewater treatment plants (WWTPs) are usually the last barrier before the water is discharged into the environment, it is important to understand the effects of these materials in the biotreatment processes, since the results in the literature are usually contradictory. We proposed the use of flow cytometry (FC) technology to obtain conclusive results. Aqueous solutions of TiO2 nanoparticles (0–2 mg mL −1 ) were used to check its toxicity effect using Pseudomonas putida as simplified model of real sludge over room light. Physiological changes in P. putida from viable to viable but non-culturable cells were observed by flow cytometry in presence of TiO2 . The damaged and dead cell concentrations were below 5% in all cases under study. Both FSC and SSC parameter increased with TiO2 dose dependent manner, indicating nanoparticles uptake by the bacteria. The biological removal of salicylic acid (SA) was also significantly impacted by the presence of TiO2 in the medium reducing the efficiency. The use of FC allows also to develop and fit segregated kinetic models, giving the impact of TiO2 nanoparticles in the physiological subpopulations growth and implications for SA removal. Graphical abstract: Highlights: SA degradation is reduced by 22% in presence of 0.1 mg mL −1 of TiO2 -NPs. Flow cytometry technique reveals TiO2 effects on bacterial viability and activity. TiO2 -NPs uptake in bacteria, since FSC and SSC increased with the NPs concentration. Bacterial growth completely inhibited for 0.5 mg mL −1 of TiO2 -NPs in SIW. Change of physiological state of Pseudomonas putida from VC into VBNC in presence of TiO2 -NPs.